Boundary Controllability of a Pseudoparabolic Equation - Qiang Tao; Hang Gao; Zheng-an Yao (Abstract and Applied Analysis, 2013)
We deal with the controllability problem for the pseudoparabolic equation by means of boundary controls. Due to the unusual spectrum of this kind of equations, we prove that the null controllability property is false. Furthermore, by the explicit solution, we show that the approximate controllability holds.